Direktori Pariwisata di Kota Pariaman - Azmi, Fajri Surya; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractÂ This paper disscuses about tourism directory in pariaman city. Writing this paper for knowing and describe about make this Directory in Pariaman City. Data were college trought direct observation and interviews on people in Pariaman City. The analysis was done with discribtive method. Based on a discussion of data analysis conclusive as follows (1) Nama of a tourist attraction (2) travel milliage (3) travel facilities (4) travel accommodations (5) travel tickets (6) plans of tourist locations (7) travel photos. Next is the to make Directory. As for the stage steps in making a directory; (a) collecting data (b) note taking data to Microsoft word (c) focus on the idea (d) creating a bookframe (e) writing directory concepts (f) determine the subject (g) a group of fabrication or grouping, and the last (h) comp directoryKeyword : Â Directory, Tourism, Pariaman City.Â